STRATEGY FOR ACCELERATING HALAL CERTIFICATION FOR SLAUGHTERERS IN THE PROVISION OF HALAL FOOD IN INDONESIA - Fauziah, Fauziah; Rachman, Abdul; Imansah, Retno Kartini Savitaningrum; Suhanah, Suhanah; Heikal, Mohd. (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Based on data from the Central Statistics Agency (BPS), the number of slaughterhouses throughout Indonesia in 2022 will be 1,644 slaughterhouses. However, the number of slaughterers who have been certified halal is still small and the number cannot be ascertained. The Slaughter is a crucial aspect and one of the important components in the halal food supply chain that plays a direct role in ensuring the halalness of the meat. Therefore, this research aims to formulate a strategy to accelerate halal certification for slaughterers to increase Muslim consumers' confidence in the quality of halal food in Indonesia. This research uses a qualitative method with a phenomenological approach by conducting observations at several slaughterhouses that have halal slaughterhouses. This research data comes from interviews with slaughter, BPJPH, LPH, RPH, and other stakeholders related to halal certification. The results of the research show that there are several acceleration strategies for halal slaughterers, namely first, increasing competency-based training programs, second, collaboration between institutions, both government and industry, third, public awareness campaigns regarding the importance of halal certification, fourth, strengthening regulations and supervision, fifth, developing home facilities and infrastructure. animal slaughter, and sixth, incentive support for slaughterers. The implementation of this strategy is expected to speed up the halal certification process for slaughterers, thereby increasing halal slaughter standards and strengthening Indonesia's position as a major producer of halal food on the global market.